Determination of total mercury in fishes of Murum, Bakun and Batang Ai hydroelectric reservoirs - Kho, Liang Ping (Universiti Malaysia Sarawak (UNIMAS), 2015)
The objectives of this study were to determine and compare THg concentration in fish sampled from three reservoir namely, Murum, Bakun and Batang Ai Hydroelectric Reservoirs. The samples were digested and diluted into 100 mL. A mercury analyser was used to determine the total mecury content in the samples. The moisture contents of 16 fish species (Barbonymus schwanenfeldii, Cyclocheilichthys apogon, Cyclocheilichthys armatus, Hampala bimaculata, Hampala macrolepidota, Hemibagrus planiceps, Lobocheilos bo, Lobocheilos falcifer, Oreochromis niloticus, Oreochromis mossambicus, Osphronemus goramy, Osteochilus hasseltii, Osteochilus waandersii, Pangasius micronemus, Puntioplites waandersi and Puntius binotatus) were ranged from 75.9% to 84.0%. Results showed that the THg content present in fish collected from Murum hydroelectric reservoir (n.d. – 3.10 mg/kg dry weight) was the highest followed by Bakun (0.19 – 2.37 mg/kg) and then Batang Ai Hydroelectric Reservoir (0.08 – 1.25 mg/kg). Statistical analysis illustrated that the concentration of THg in fish species from each reservoirs and among the three reservoirs were significantly different (P < 0.05) from each other. Higher trophic level of fish species tends to accumulate more Hg than lower trophic level of fish species. This may be associated to the impoundment history as literature suggests that fishes caught from a newly impounded dam tend to have higher mercury content within 5 to 35 years after impoundment.